The Development of the European Union Legislative Framework Against Money Laundering and Terrorist Financing in the Light of International Standards - Van Ha, Thai (Technium Social Sciences Journal, 2021)
This article examines the recent evolution of the European Union (EU) anti-money-laundering and counter-terrorist financing legal framework in the connection with the main international standards in the field, with a special concentration on the Financial Action Task Force (FATF) Recommendations, and then highlights the potential risks of money laundering and terrorist financing and areas for improvement when adopting these international standards.